Fountain University’s strategies of islamizing knowledge: an overview (2011)
The intention of this paper is to bring to the fore the strategies of Fountain University via-a-vis knowledge Islamization. The approach adopted in this regard is basically descriptive coupled with personal observation of the writer. In this paper attempt is made to probe into the historical background of this programme with a particular reference to Nigerian experience of de- Islamization process which eventually necessitated the adoption of the programme in Nigeria. As a background to the study, a synopsis about the university is highlighted coupled with the methods being adopted to ensure not only the acquisition of sound knowledge but also the moral principle- through these strategies. The paper concludes that the lofty goal of this programme will be better achieved if all the recommendations made are faithfully observed.